Association Between Neighborhood Opportunity, Cognitive Function, and Brain Structure in Youths - Lan Zhou; Tianying Cai; Ka I Ip (Biological Psychiatry Global Open Science)
Background: Access to essential neighborhood opportunities (e.g., quality education, nutritious foods, clean air) is critical for development, but the influence of these factors on neurocognition remains unclear. Leveraging the ABCD (Adolescent Brain Cognitive Development) Study, we examined associations between neighborhood opportunity, cognitive function, and brain structure. Methods: Participants were 10,463 (ages 9–10 years) children. Neighborhood opportunity was measured by the Child Opportunity Index (COI 2.0), which assesses educational, health/environmental, and social/economic opportunities. Cognitive function was measured via the NIH Toolbox Cognition Battery, and T1-weighted imaging provided brain structural measures. Results: Youths living in higher-opportunity neighborhoods exhibited better performance across all cognitive measures (β = 0.11–0.37, p < .001) and larger whole-brain gray matter volume (β = 0.10, p < .001), surface area (β = 0.06, p < .001), cortical thickness (β = 0.11, p < .001), and specific brain volume regions implicated in cognitive function. These associations persisted after controlling for demographic and household factors (e.g., material hardship, family conflict, and parental education). Relative weight analyses revealed that socioeconomic neighborhood opportunities had the strongest influence on cognitive function (33.35%–51.56%) and brain measures (48.95%–60.98%), although educational and health/environmental opportunities also contributed uniquely. Structural equation modeling found that whole-brain gray matter volume and surface area mediated the relationship between COI and cognitive outcomes at the 2-year follow-up, with regional effects in the dorsolateral prefrontal cortex and anterior cingulate cortex. Conclusions: Neighborhood opportunity is a critical factor that shapes neurocognitive development, beyond effects of household-level indicators and neighborhood deprivation. The findings highlight the importance of using an asset-based approach to understand how multiple neighborhood resources may foster neurocognitive development and advance health equity for youth.